Estimativa de vazão mínima em pequenas bacias hidrográficas - Pogian, Mauricio Freixo (2016)
Proper knowledge of water availability is a key factor for the proper management of water resources in a given region. However, in many places, information and data are scarce and not always available in an adequate space and scale. In this sense, the estimation of characteristics discharge of a watercourse, in particular the minimum discharge rates used as references for the granting processes of water resources, becomes a support tool for water management and planning. Several methods have been tested and used to estimate the stream flow. In places without monitoring (no data) the discharge estimative is generally based on spatial similarity of functions, variables and hydrological parameters from basins in the same region, allowing information transferences between locations with data and locations without data, called regionalization studies. So, this study aims to improve the minimum flow estimations in small watersheds. Existents methods were researched and analyzed qualitatively, aiming to highlight aspects that support applications in small basins. Two estimation methods (Traditional Regionalization and Silveira method) were selected for a qualitative evaluation in eight river basins in the states of Minas Gerais and Espirito Santo, with drainage areas ranging from 4.9 to 210.3 km². The traditional method of regionalization used by managers and available in literature showed, in general, better results for Q90 and Q7,10 estimative The worst results obtained by Silveira Method are probably due to the uncertainties related to the quality and quantity of input data. Finally, the guidelines proposed to allow an improvement of the estimative indicates the need for increased hydrological monitoring, as also the need of the development and improvement of the estimation methods, mainly those based on the ecological flow concept and that consider other aspects than the hydrological ones